Method for extracting Raman spectra characteristic variables of biological sample based on Hilbert–Huang transform. (9th March 2020) - Zhao, Xiaoyu; He, Yan; Liu, Zihao; Zhang, Wei; Tong, Liang
Abstract: Because Raman peaks of the biological sample are superimposed on each other, the use of characteristic peak attribution is limited to some extent. In this study, we show that Hilbert–Huang transform (HHT) provides a Raman spectral feature extracting method, especially for biological samples. First, the empirical mode decomposition algorithm was used to decompose Raman spectra into intrinsic mode functions (IMFs). It is worth noticing that the IMF frequency is single or nearly single, so its further transformation (instantaneous amplitude, instantaneous angle, instantaneous angular frequency, Hilbert spectrum, and Hilbert marginal spectrum) from Hilbert processing is monotonous instead of the raw overlapping. Then, the Hilbert marginal spectrum was selected by one‐way analysis of variance and related with the rice type to establish a partial least squares regression (PLS) model with a 95.00% accuracy. This result is better than those based on characteristic variables screened by PLS, interval PLS, principal component analysis, independent component analysis, successive projections algorithm, haar, db, and coif (85.00%, 90.00%, 82.50%, 77.50%, 90.00%, 92.50%, 80.00%, and 85.00%). These results illustrate that HHT can accurately extract the characteristic variables from biological Raman spectra. The classification accuracy based on HHT is slightly lower than those based on bior 2.4, three‐layer decomposition (97.50%) and sym 5, five‐layer decomposition (97.50%). Significantly, no parameters need to be set such as the wavelet mother function and the decomposition layer in the HHT feature extraction process. This paper provides a HHT method for Raman spectral feature extraction, which is simple and effective. Abstract : In this study, we show that Hilbert‐Huang transform (HHT) provides a Raman spectral feature extracting method, especially for biological samples. Some frequency points in Hilbert marginal spectrum was selected to be Raman spectra characteristic variables. The experiments show that the HHT method can be used for the Raman feature extraction as well as common methods, such as PLS, iPLS, SPA, WA, PCA and ICA, but the operation is simple.